Study of the anticorrosive behavior of samarium as a corrosion inhibitor in multilayer systems for aluminum alloy - José Antonio Cabello Mendez; Ailed Arguelles Rojas; José de Jesús Pérez Bueno; Yunny Meas Vong (Scientific Reports, 2023)
Abstract This study shows a multilayer system based on samarium compounds as a corrosion inhibitor and a continuous SiO2 layer by atmospheric pressure plasma jet (APPJ) as a protective barrier for aluminim alloy AA3003. One of the main advantages of this new coating is that it does not require vacuum chambers, which makes it easy to incorporate into production lines for automotive and aeronautical components, etc. The deposit of samarium corrosion inhibitor was carried out by two methods for comparison, the immersion method and a novel method to deposit corrosion inhibitor by APPJ. The multilayer system generated was homogeneous, continuous, adherent, and dense. The electrochemical behavior shows that the samarium compound was completely oxidized on coatings by the immersion method and favors corrosion. The APPJ deposition method shows a protective behavior against corrosion by both samarium compounds and silica depositions. XPS analyses show that the amount of Sm(OH)3 increases by the APPJ method compared with the immersion method since the spectrum of O1s is mainly controlled by OH. It was determined that the best processing times for the electrochemical study of the multilayer system were 40 min for the immersion method and 30 s for the APPJ method for the layer of corrosion inhibitor. In the case of the SiO2 barrier layer by APPJ, the best time was 60 s of exposure to the plasma jet and this coating could reduce the corrosion of AA3003 by 31.42%.